Development and Reliability of a User-friendly Multicenter Phenotyping Application for Hemorrhagic and Ischemic Stroke - Owolabi, Mayowa (J Stroke Cerebrovasc Dis, 2017)
BACKGROUND: AIM on ClearCanvas Enriched Stroke- phenotyping Software (ACCESS) is a novel standalone computer software application that allows creation of simple standardized annotations for reporting brain images of all stroke types. We developed the ACCESS application and determined its inter-rater and intra-rater reliability in the Stroke Investigative Research and Educational Network (SIREN) study to assess its suitability for multicenter studies. METHODS: One hundred randomly selected stroke imaging reports from five SIREN sites were reevaluated by four trained independent raters to determine inter-rater reliability of ACCESS (version 12.0) software for stroke phenotyping. To determine intra-rater reliability, six raters reviewed the same cases previously reported by them after a month interval. Ischemic stroke was classified using the Oxfordshire Community Stroke Project (OCSP), TOAST and ASCO protocols, while hemorrhagic stroke was classified using the SMASH-U protocol in ACCESS. Agreement among raters was measured with Cohen’s kappa statistics. RESULTS: For primary stroke type, inter-rater agreement was 0.98 (95%CI: 0.94–1.00) while intra-rater agreement was 1.00 (95%CI: 1.00). For OCSP subtypes, inter-rater agreement was 0.97 (95%CI: 0.92–1.00) for the Partial Anterior Circulation Infarcts (PACI), 0.92 (95%CI: 0.76–1.00) for the Total Anterior Circulation Infarcts(TACI) and excellent for both Lacunar Infarct (LACI) and Posterior Circulation Infarcts (POCI). Intra-rater agreement was 0.97 (0.90–1.00) while inter-rater agreement was 0.93 (95%CI: 0.84–1.00) for TOAST subtypes. Inter-rater agreement ranged between 0.78 (cardioembolic) to 0.91 (large artery atherosclerotic) for ASCO subtypes and was 0.80 (95%CI: 0.56–1.00) for SMASH-U subtypes. CONCLUSION: The ACCESS application facilitates concordant and reproducible classification of stroke subtypes by multiple investigators, making it suitable for clinical and multicenter research.